A small number of objective function weight vectors is sufficient for automated treatment planning in prostate cancer. (21st September 2018) - Goli, Ali; Boutilier, Justin J; Craig, Tim; Sharpe, Michael B; Chan, Timothy C Y
Abstract: Current practice for treatment planning optimization can be both inefficient and time consuming. In this paper, we propose an automated planning methodology that aims to combine both explorative and prescriptive approaches for improving the efficiency and the quality of the treatment planning process. Given a treatment plan, our explorative approach explores trade-offs between different objectives and finds an acceptable region for objective function weights via inverse optimization. Intuitively, the shape and size of these regions describe how 'sensitive' a patient is to perturbations in objective function weights. We then develop an integer programming-based prescriptive approach that exploits the information encoded by these regions to find a set of five representative objective function weight vectors such that for each patient there exists at least one representative weight vector that can produce a high quality treatment plan. Using 315 patients from Princess Margaret Cancer Centre, we show that the produced treatment plans are comparable and, for of cases, improve upon the inversely optimized plans that are generated from the historical clinical treatment plans.